Stakeholder Consultation and Decision Report - Altshul, Helen J. (CGIAR System Organization, 2025)
This report captures perspectives from the CGIAR’s staff, researchers, and cross-cutting specialists on the feasibility and support needs for integrating responsible innovation and scaling. It summarizes insights from consultations, highlighting perceived barriers, enabling factors, and shared priorities for advancing responsible practices in research and scaling.